Marriage Registration in Islamic Law - Sitizalikha Sitizalikha; Abdullah Abdullah; Nurazizah Nurazizah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Getting a life partner is a human partner in accordance with their nature. Living together must be carried out in an official way, namely through marriage. Marriage must be carried out with the provisions that have been set in Islam. In addition, the state also requires registration of marriages. This research is entitled Marriage Registration in Islamic Law. This study discusses how the views of Islamic law on marriage registration at the Office of Religious Affairs (KUA) and the consequences of marriages that are not registered at the Office of Religious Affairs (KUA). This research is library research. This type of research is a type of qualitative research with a normative approach that is descriptive-analytical. This research concludes thatIslamic law does not view marriage registration as a pillar or condition for a valid marriage. Marriage is still valid as long as the pillars and conditions are met. Marriages that are not registered with the Office of Religious Affairs (KUA) are considered a mistake in the view of Islamic law, because they do not obey Allah's orders in terms of obeying government regulations. Marriage registration is a must in juridical studies. The state does not declare illegitimate marriages that are not registered at the Office of Religious Affairs (KUA). However, the marriage is not under the legal umbrella, so the state is not responsible for the impacts that occur from the marriage in the future.